Identification of Bacteria from Soil of Cameron Highlands (Asian Journal of Plant Biology, 2014)
The bacteria are a large group of unicellular microorganisms. Bacteria are ubiquitous in everyhabitat on Earth for example growing in soil, radioactive waste, water and as well as in organicmatter and the live bodies of plants and animals. They are small cells, found in the environmentas either individual cells or aggregated together as clumps. This study was aimed to identify thebacteria from soil sample obtained from Cameron Highlands. Eight samples were inoculated onNutrient Agar plate. After obtaining pure culture, stock cultures on Nutrient Agar slant andglycerol stock were prepared and the samples were kept in -20ËšC. Next the samples werefurther studied using microscopic observation. From this technique, seven Gram positivebacteria and one Gram negative bacteria were obtained. The Gram positive rod shaped wasanalyzed further using the molecular technique 16S rDNA using pA and pH primers. Then thesample proceeds to bulk. PCR product of approximately 1kb in size was obtained. The purityvalue of the DNA sample obtained was 1.16 A260/280. The sample was sent for sequencing toNHK Bioscience and Macrogreen (Korea). Only one sample showed positive for 16S rDNAfragments which were analyzed using Basic Local Alignment Search Tool (BLAST) forbacterial identification. The data analysis of the sequence shows that the bacterium obtainedwas Bacillus pumilus strain.
Keywords: Bacteria, 16S rDNA, BLAST, Bacillus pumilus